Split NPs lower than second position in Croatian: A cognitive account - Peti-Stantić, Anita (Array, 2010)
The problems of scrambling, which I understand as a narrow syntactic operation whose phonological effects at the syntax–phonology interface correlate with semantic effects at the syntax– semantic interface, along with clitic clustering and positioning, have been some of the most challenging not just from a Slavic perspective, but also for general theories of syntactic and prosodic structure. Although all western South Slavic languages are canonical scrambling languages, each of them exhibits peculiarities that have not been adequately explained in contemporary Slavic linguistic scholarship. Contrary to common assumptions about strict restrictions in the distribution of clitics, there are several types of sentences in contemporary Croatian which contradict expected clitic placements and splitting possibilities. Although these types of sentences are frequently attested, one can observe a high degree of variation in judgements about the acceptability of different kinds of splitting, both across speakers and across languages, and they are notably absent from previous discussions of scrambling and clitic placement. I attribute this to the fact that the majority of research has been couched in a syntactocentric approach, concentrating on typical second-position examples that can be fitted easily into standard theoretical models, at the expense of broader empirical coverage. Although the following sentences differ radically from what has been reported in the literature, I hope to show that they can be consistently explained within a framework of parallel architecture (Jackendoff 2002, Culicover & Jackendoff 2005) which has considerable points of contact with cognitive approaches: Od jučer ga prodaje za velike novce. (no splitting ; neutral reading) ‘Since yesterday (s)he’s selling it for big bucks.’ Za velike ga novce prodaje od jučer. (neutral reading preferred) ‘Since yesterday (s)he’s selling it for big bucks.’ Od jučer prodaje za velike ga novce. ‘Since yesterday (s)he’s selling it for big BUCKS.’ or ‘Since yestedrday (s)he’s selling it for BIG bucks.’ or JUST ‘Since yesterday (s)he’s selling it for big bucks. *Od jučer prodaje za ga velike novce. (Bold = clitic, underline = constituent being split) I intend to address this inadequacy between the data and present accounts and concentrate on the connection between scrambling mechanisms and clitic cluster placements outside the predicted second position. Taking into account the fact that scrambling is semantically driven, so that it affects syntactic, semantic and information- structural properties of a sentence, I will explore clitic positioning lower than second position (“clitic third” or “delayed clitic placement”), especially the ability of a clitic or a clitic cluster to split Noun Phrases (NPs) lower than second position. Building on the obvious conflict between free word order and restrictions of clitic placement, I will try to identify the semantic combinatoriality features of clitic placement lower than the second position and their ability to split NPs. I will focus especially on information structure (topic vs. focus vs. common ground), since the placements lower than second position, for as much as I know now, all appear to be dependent on specific contexts. The controversy over whether clitic placement is fundamentally syntactic or prosodic, in conjunction with the data I have collected that contradict previous analyses, leads me to conclude that there is considerable room for a new approach to clitic placement and a new interpretation of the data.